(untitled) (Journal of Imam Al-Kadhim College, 2023)
The research has attempted to provide a critical evaluation of Hassan Hanafi’s project in the field of humanization. He was a fabricated thinker rather than presented original work in the field of humanism. He has been tried to revolutionize philosophical and social concepts in Islamic societies by borrowing approaches from Western thinkers whose historical contexts within which they work differ from that of Islamic thought ideologically and epistemologically. In this regard, it is completely opposite to Muhammad Arkoun’s more original project when he highlights historical stations in Islamic thought that clearly embodied the centrality of man and his values, to make them starting points for Islamic modernity. While Hanafi tries to bring Islamic thought to the standards of Western modernity and tries to employ Western concepts in the Islamic environment. Therefore, we find Hanafi invoking Feuerbach’s concepts, the contexts of the development of Western thought, and Husserl’s concepts, 0t make them starting points for intellectual transformation in Islam. The research will attempt to explain Hanafi’s leftist revolution, which began with Islamic thought and did not end with the coup revolution.